2001
DOI: 10.1074/jbc.m105668200
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-dependent Dissociation of Oligomeric Complexes of G Protein-coupled Cholecystokinin Receptors Demonstrated in Living Cells Using Bioluminescence Resonance Energy Transfer

Abstract: Dimerization of some G protein-coupled receptors has recently been demonstrated, but how widespread this phenomenon might be and its functional implicationsare not yet clear. We have utilized biophysical and biochemical techniques to evaluate whether the type A cholecystokinin (CCK) receptor can form oligomeric complexes in the plasma membrane and the impact of ligand binding and signaling on such complexes. We investigated the possibility of bioluminescence resonance energy transfer (BRET) between receptor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 39 publications
8
117
0
Order By: Relevance
“…Likewise, the presence of the bulky heterotrimeric G-protein complex associated with the receptor (since Gproteins, when bound to membrane receptors, could be considered as equivalent to cytoplasmic domains of membrane proteins) could further reduce (over the differences arising due to molecular mass of G-proteins) receptor diffusion, which would be partially relieved when the Gprotein dissociates from the receptor. Another possibility could be that the increase in receptor diffusion could reflect changes in the oligomeric state of the receptor, as has been shown for the δ-opioid receptor [41], and the cholecystokinin receptor [42] or their partitioning into or out of domains proposed to exist on the cell surface [7,9]. Incidentally, there is growing evidence on the compartmentalized localization of G-proteins in cholesterol-rich membrane domains [43] that have been reported to diffuse as separate entities on the membrane [44].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the presence of the bulky heterotrimeric G-protein complex associated with the receptor (since Gproteins, when bound to membrane receptors, could be considered as equivalent to cytoplasmic domains of membrane proteins) could further reduce (over the differences arising due to molecular mass of G-proteins) receptor diffusion, which would be partially relieved when the Gprotein dissociates from the receptor. Another possibility could be that the increase in receptor diffusion could reflect changes in the oligomeric state of the receptor, as has been shown for the δ-opioid receptor [41], and the cholecystokinin receptor [42] or their partitioning into or out of domains proposed to exist on the cell surface [7,9]. Incidentally, there is growing evidence on the compartmentalized localization of G-proteins in cholesterol-rich membrane domains [43] that have been reported to diffuse as separate entities on the membrane [44].…”
Section: Discussionmentioning
confidence: 99%
“…These modifications were incorporated into a native human SecR open reading frame (ORF) that was subcloned through an EcoRV/SmaI blunt-end ligation from pBKCMV/SecR (28) into the cytomegalovirus-driven eukaryotic expression vector pcDNA3 (Invitrogen). The same mutations also were incorporated into Rlu and YFP carboxyl-terminally tagged versions of the same SecR coding sequence, minus the 5' and 3' untranslated regions (35). Construction of pcDNA3/SecR-CFP (27) and pcDNA3/CCKBR-YFP (36) were described previously.…”
Section: Receptor Mutagenesismentioning
confidence: 99%
“…Acceptor fluorescence was confirmed for all YFP-tagged mutants by direct excitation at 480 nm. BRET ratios (35) were calculated from baseline-corrected peak integrations as follows: [Em 510−590 -(Em 440−500 *Cf)]/Em 440−500 . The correction factor Cf = Em 510−590 /Em 440−500 defined the amount of signal in the acceptor portion of the spectrum that was attributable to donor bioluminescence, and was calculated separately for each experiment from cells expressing the appropriate Rlu-tagged SecR mutant alone.…”
Section: Bret Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that dimerization of the CCK receptor is not required for its biological activity, even though such dimers have been suggested to exist in bioluminescence resonance energy transfer studies (Cheng & Miller 2001). Of interest, CCK agonist binding to its receptor was shown to dissociate CCK receptor dimers in that study (Cheng & Miller 2001). The functional importance of CCK receptor oligomerization is unclear at the present time.…”
Section: Photoaffinity Labeling Studiesmentioning
confidence: 91%